AN INVESTIGATION OF PLACE NAMES IN ALANYA (ALAİYE) SANDJAK ACCORDING TO RECORDS OF THE SIXTEENTH CENTURY - Selim Hilmi ÖZKAN (Fırat University, 2019)
Alanya is an important touristic and agricultural city on the Mediterrenean Coast of Turkey. The city was also important during Ottoman and pre Ottoman period for agricultural and trade as well. The purpose of this study was to explore the XVIth century of Alâiye Sandjak’s place (210 villages, hamlets, communities, lodges, mountain pastures and tribal names) and their charasteristics. The data was collected from 1500, 1530, 1555 Ottoman Tax Registers (Tahrir Defterleri). In this study, more than 210 villages, hamlets, communities, a small Islamic monastery, place names, plateau, and mountain were investigated. In addition to this, over 132 pieces of nomadic and tribal names were evaluated according to their name. The study revealed that majority of these names are in Turkish and same of name of the places are transformed into Turkish from their original names.